If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -1) + -3(x + -2) = 10 + 5x Reorder the terms: 4(-1 + 2x) + -3(x + -2) = 10 + 5x (-1 * 4 + 2x * 4) + -3(x + -2) = 10 + 5x (-4 + 8x) + -3(x + -2) = 10 + 5x Reorder the terms: -4 + 8x + -3(-2 + x) = 10 + 5x -4 + 8x + (-2 * -3 + x * -3) = 10 + 5x -4 + 8x + (6 + -3x) = 10 + 5x Reorder the terms: -4 + 6 + 8x + -3x = 10 + 5x Combine like terms: -4 + 6 = 2 2 + 8x + -3x = 10 + 5x Combine like terms: 8x + -3x = 5x 2 + 5x = 10 + 5x Add '-5x' to each side of the equation. 2 + 5x + -5x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + 0 = 10 + 5x + -5x 2 = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 2 = 10 + 0 2 = 10 Solving 2 = 10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2a+1=5a-2/2 | | X-1/4=6 | | 3k-2=4k-4 | | (x-35)+(x-46)+x+.5x=360 | | Y+2y+15=180 | | 3(4+2x)=18-6x | | (4x^2-x)-3x^2= | | 2x+5(x-3)=x+2 | | 5-k=36 | | 34=-17w | | 63=-3y | | 12(2+7)-24/12 | | 8x+1=7x-9 | | 6(4+x)=66 | | 6x-(3X-7)=29 | | 7x-(2x-22)=67 | | 4(x-5)=5(x-4)-x | | 6x1/2y=3 | | -4/3x+7/2=-3/4x-2 | | M=9n | | 2x/3-1=x-2/2 | | 5(2ab)= | | 5x^2-13-6=0 | | 2(5x+1)=92 | | 12-x=-16 | | 9x+11-2x=10-11x-12 | | (6+2)(28-27)= | | 5(-7x+5)=-10 | | -21/2*46/7 | | (6+2)(28-27)5= | | 4t-4=16-t | | -8-3x=22 |